إجراءات منح القرار المتعلق برخصة البناء - دراجي, عبد القادر (University of Eloued جامعة الوادي, 2014)
هناك حلقة مفقودة في العملية الإدارية حيث أن القوانين والتنظيمات التي تنص على تنظيم النشاط العمراني موجودة، نحو (تنظيم الرقابة الإدارية لأشغال البناء وفرض احترام أدوات التعمير) والمكلف بتطبيق هذه القوانين محدد وهي السلطة الإدارية والإجراءات التي تطبق على المخالفين في ميدان البناء والتعمير معروفة لديهم، إلا أنه ورغم كل تلك فظاهرة البناءات الفوضوية والاستيلاء غير الشرعي للأراضي مستمرة فالحلقة المفقودة في تطبيق القوانين على المخالفين، فالواقع يثبت الوضع الغير سليم الذي آلت إليه الأوضاع في هذا المجال، جراء عدم الصرامة في تطبيق القوانين على المخالفين. Although the laws and regulations that provide for the regulation of urban activity exist, and the body tasked with the application of these laws is the administrative authority, and procedures that apply to the violators in the building and construction field known to them, but the phenomenon of chaotic buildings and seizing illegal, and the illegal seizure of land is a continuous. The problem is not to apply the law on violators, the reality proves improper current status of the situation in this field, by the lack of rigor in the application of laws on violators.
مقال بمجلة البحوث والدراسات
Keywords: النشاط الحضري - رخصة البناء - السلطة الإدارية - بناء فوضوي; -urban activity - building permit - administrative authority - chaotic building-